Influence of Support Material of PtSnNiGa/C Electrocatalysts for Ethanol Oxidation - Santos, Deise M.; Paganoto, Giordano T.; Queiroz, Maria A. R.; Guimarães, Marco C. C.; Ribeiro, Josimar (Orbital: The Electronic Journal of Chemistry, 2017)
Ethanol is a promising alternative source for fuel cells due to its low toxicity and high power density. However, the cleavage of the C-C bond, CO poisoning, and low electrocatalyst stability are still considered crucial issues. To overcome this limitation, binary, ternary and quaternary electrocatalysts have been investigated along with new carbon supports. This paper presents a physicochemical and electrochemical investigation of quaternary PtSnNiGa/C electrocatalysts supported on Vulcan XC72 and Printex-L6 carbons and also a carbon produced by natural gas pyrolysis in an Argon plasma torch (Black Plasma). The electrochemical characterization was performed through cyclic voltammetry, chronoamperometry, chronopotentiometry and electrochemical impedance spectroscopy in the presence of ethanol 1.0 mol L-1. Energy dispersive X-ray spectroscopy, X-ray diffraction, Raman spectroscopy and transmission electron microscopy were also carried out for physicochemical characterization. The electrochemical results show that the quaternary electrocatalysts supported on Vulcan XC72 and Printex-L6 carbons display a high current normalized by Pt mass and are more stable than the electrocatalyst supported on Black Plasma. In addition, the quaternary electrocatalysts with reduced Pt loading display better electrocatalytic activity towards the EOR compared to high Pt loading electrocatalysts. DOI: http://dx.doi.org/10.17807/orbital.v9i3.949